Enhancing Public Sector Outcomes through Fiscal Reform Strategies in Developing Countries - Setiadi; Wijayanti, Dian; Siswanti, Tutik (Yayasan Sinergi Kawula Muda, 2025)
Tax policy reforms have emerged as a crucial tool for enhancing public sector performance in developing countries. This study aims to synthesize recent literature on the relationship between fiscal reforms and public service outcomes. Using a narrative review methodology, we collected and analyzed peer-reviewed studies from Scopus, Web of Science, and JSTOR. Keyword-based searches and defined inclusion criteria ensured relevance and quality in the selection process. The review reveals that strategic tax reforms can significantly improve revenue generation, promote equity, and enhance public service delivery. Key themes identified include the impact of tax policy on domestic resource mobilization, the role of tax incentives in shaping public spending priorities, and the importance of institutional capacity in sustaining reforms. Evidence from countries such as Rwanda, Colombia, and Indonesia demonstrates that aligning tax strategies with governance improvements can yield measurable benefits. However, systemic challenges such as weak institutions, political instability, and limited administrative capacity persist, constraining reform effectiveness. The findings suggest that future research should incorporate mixed-methods approaches and focus on underrepresented regions and qualitative dimensions of reform. Policymakers are encouraged to adopt adaptive, inclusive, and transparent fiscal strategies tailored to local contexts. By doing so, tax reforms can serve as powerful levers for promoting equitable growth and efficient public sector performance in the face of evolving global challenges.